Successful restoration of failed Achilles tendon surgery with semitendinosus and gracilis tendon graft: a case report - Hung, Yu-Tun; Alizargar, Elaheh; Alizargar, Javad; Hung, Kun-Chin; Chen, Chien-Min; Pan, Ru-Yu (Frontiers in Surgery, 2023)
Objective This case presentation aims to highlight the challenges and outcomes associated with a partial tear of the Achilles tendon (AT) in an elite marathon runner. The objective was to restore tendon anatomy and optimize strength recovery through surgical intervention. Method We present the case of a marathon runner who suffered a partial AT tear and underwent an initial surgery that failed. A revision surgery was then performed using a semitendinosus and gracilis tendon graft. Results The patient underwent surgery 14 weeks after the initial AT injury, but unfortunately experienced a complete AT tear after 6 months. However, the novel aspect of this case is the successful restoration of the failed double-row suture technique through the utilization of a semitendinosus and gracilis tendon graft. Notably, the graft remained intact even under high tendon loading during the 2-year follow-up period. Conclusion Differential diagnosis should consider partial tears of the AT as a possible diagnosis in the patients with heel pain. Furthermore, it is crucial to prioritize a well-paced post-surgical rehabilitation process in AT surgeries. In cases of failed AT surgery, the utilization of gracilis and semitendinosus tendon grafts can serve as viable options for repairing reruptures.